Peg+Cat and problem solved (Edma 0-6: Educación Matemática en la Infancia, 2017)
We continue with our interest in those animated cartoons movies and series for the little ones in which mathematics receives special attention. On this occasion, we discuss a production that is currently being broadcasted, awarded with two Emmy Awards in the 2016 edition. It is Peg+Cat, on which we perform an initial analysis and address the treatment of measurement issue. We will observe that essential aspects of the measurement processes, such as the ideas of conservation and transitivity, the establishment of arbitrary reference units and, even, the equivalence between units, are inserted naturally in the narrative of the episodes that we comment.
Keywords: Early Childhood Education; Mathematics; Animated cartoons; Audio-visual fiction